Awareness of Small Scale Farmers and Their Willingness to Adopt the Growth Enhancement Support (GES) Scheme In Oyo State, Nigeria (2018)
Fertilizer and seeds have been recognized as two of the most critical farm inputs needed to enhance and sustain increased farm productivity in Nigeria. However, total fertilizer use remain far below the potential and economic demand. This study examined the awareness of small-scale farmers and their willingness to adopt the Growth Enhancement Support (GES) scheme. The scheme encourages the resource-constrained farmer and the critical actors in the fertilizer value chain, to work together to improve productivity, household food security and income. Data were obtained from 200 farmers, selected through a multi-stage sampling technique. Probit and Logistic Regression models were employed for analysis. Results showed that most of the respondents were aware of the GES scheme as well as the type of farm inputs supported under the scheme. While factors such as years of farming experience (β= 0.078), farm size (β=1.648) and membership of farmers’ association (β=0.053) significantly influenced the level of awareness of the farmers about the scheme at 5 and 1% level of significance respectively, farmers’ willingness to adopt the scheme was influenced by land ownership (1%), access to subsidized inputs (1%) among others. Awareness and access to timely and relevant information about a scheme play a central role in the adoption decision process of small-scale farmers. To enhance the adoption of schemes such as the GES, there is the need for capacity building programmes as well as the identification of the key determinants of the willingness of smallscale farmers to adopt such schemes.